On hybrid overlay-underlay dynamic spectrum access: Double-threshold energy detection and markov model - Jiang, X; Wong, K; Zhang, Y; Edwards, D (2013)
In this correspondence, we propose a hybrid strategy that combines overlay and underlay dynamic spectrum access (DSA) schemes. Utilizing a double-threshold energy detection method, unlicensed or secondary users (SUs) can switch between full- and partial-access modes dynamically. A Markov chain model is developed to derive performance metrics for evaluating the proposed strategy. Numerical results show that the proposed strategy can greatly improve the system interfering probability performance. In addition, SUs can adjust the access probability of partial-access mode to tradeoff between throughput and interfering probability performance. © 1967-2012 IEEE.